KAJIAN PUSTAKA TENTANG PENGARUH VARIASI KADAR AIR DAN PENAMBAHAN MATERIAL ADDITIVE TERHADAP KARAKTERISTIK KUAT GESER TANAH LEMPUNG - Yuki Panie; Monica T Andries; Sudarno P Tampubolon; Efendy Tambunan (Jurnal Rekayasa Teknik Sipil dan Lingkungan - CENTECH, 2026)
This study examines the effect of moisture content and the addition of various additives on the shear strength behavior of clay soils through a comparative literature review of 13 previous studies. Clay soil, known for its low bearing capacity and high sensitivity to moisture changes, frequently requires stabilization to enhance its strength. The results indicate that an increase in moisture content generally decreases soil shear strength due to a reduction in cohesion and the internal friction angle, particularly when it exceeds the optimum moisture content. Conversely, the addition of additives such as cement, lime, rice husk ash, and polypropylene fibers shows a significant increase in shear strength. Cement and lime provide chemical bonding, whereas ash and fibers enhance physical resistance. The combination of these materials yields the most effective results. This study utilizes a qualitative-comparative analysis by gathering data from laboratory-based journal publications that include direct shear tests and unconfined compression tests. The findings emphasize the importance of controlling moisture content and material composition in geotechnical engineering and slope stability. It is concluded that moisture content is a dominant factor that negatively impacts shear strength, whereas additives serve as efficient reinforcers. Future research is suggested to involve laboratory experiments on various types of clay soils and to utilize computational modeling for more accurate predictions regarding the interaction between moisture content and stabilization materials. Keywords: Additives; Clay soil; Moisture content; Shear strength; Soil stabilization